GAMBARAN KEPEMILIKAN JAMBAN SEHAT DI DESA KALITENGAH KECAMATAN PURWANEGARA KABUPATEN BANJARNEGARA TAHUN 2018 - Dwi Atin Faidah; Joko Malis Sunarno (Jurnal Ilmiah Medsains, 2018)
Universal access to adequate sanitation are basic needs and human rights. One of the goals of the 17 Sustainable Development Goals (SDGs) at the sixth point is to ensure the availability of clean water and sustainable sanitation for everyone (WHO, 2017). The results of Basic Health Research (Riskesdas) in 2013 showed that the number of households in Indonesia using latrines with septic tanks reached 66%. The number of households that still do open defecation is 12.9%. One of the sub-districts in Banjarnegara whose coverage of access to healthy latrines is still low is Purwanegara Sub-district which is 60,04%. Based on a preliminary survey in the village of Kalitengah in Purwanegara sub-district, the coverage of healthy latrine access is still very low at 28%. The purpose of this study was to find out the description of ownership of healthy latrines in Kalitengah Village, Purwanegara District. This research is a descriptive study with a cross sectional approach. The study was conducted in July-September 2018. The sample in this study were 93 families. Data collection is done through interviews and observations. Interviews with questionnaires were used to reveal the characteristics of respondents. Direct observation in the field to observe latrine sanitation conditions. The statistical design used is univariate analysis. The results showed that the characteristics of respondents were dominated by the age of 45-50 years, male gender (66,7%), primary school education level (63,4%), employment as a farmer (49,5%) and monthly income less than MSEs (61,3%). The ownership of healthy latrines has only reached 6,.12%. It is hoped that the government will provide assistance in the form of latrines that meet the requirements for residents who do not have latrines.